Synthesis of novel 2-propenoyl amides, esters, heterocyclic compounds and their screening as antifungal and antibacterial agents - El-Ziaty, Ahmed; Abdalh, Abdelaal; Hamed, Ashraf; Shiba, Sayed; Abdullha, Abdelhafed (European Journal of Chemistry, 2012)
Compound, 2-cyano-3-(2ˊ,4ˊ-dichlorophenyl)-2-prpoenoyl chloride, 3, was reacted with nitrogen, sulfur, and oxygen nucleophilic reagents to give new 2-propenoyl amide and ester derivatives. Some of these derivatives were cyclized under the reaction conditions and/or with POCl3 or Ac2O to give new derivatives of heterocyclic systems. Some of these compounds were tested as antibacterial and antifungal agents.